Heuristics and metaheuristics for dynamic management of computing and cooling energy in cloud data centers. (26th June 2018) - Arroba, Patricia; Risco‐Martín, José L.; Moya, José M.; Ayala, José L.
Summary: Data centers handle impressive high figures in terms of energy consumption, and the growing popularity of cloud applications is intensifying their computational demand. Moreover, the cooling needed to keep the servers within reliable thermal operating conditions also has an impact on the thermal distribution of the data room, thus affecting to servers' power leakage. Optimizing the energy consumption of these infrastructures is a major challenge to place data centers on a more scalable scenario. Thus, understanding the relationship between power, temperature, consolidation, and performance is crucial to enable an energy‐efficient management at the data center level. In this research, we propose novel power and thermal‐aware strategies and models to provide joint cooling and computing optimizations from a local perspective based on the global energy consumption of metaheuristic‐based optimizations. Our results show that the combined awareness from both metaheuristic and best fit decreasing algorithms allow us to describe the global energy into faster and lighter optimization strategies that may be used during runtime. This approach allows us to improve the energy efficiency of the data center, considering both computing and cooling infrastructures, in up to a 21.74% while maintaining quality of service.